Underpricing of the Malaysian Initial Public Offerings (IPOs) - Shari, Wahidah (UI Scholars Hub, 2025)
This study evaluates the short-term performance of 469 Malaysian IPOs between 2002 and 2020. Previous studies have found that IPOs are underpriced in the short-term yet underperform in the long term. The short-term underpricing describes the phenomenon characterized by a significant increase from the offer price to the first day of closing price. The finding shows that Malaysian IPOs are significantly underpriced by 24.6% using offer-to-close return (OTC), which confirms the findings reported in previous literature. Separating OTC to offer-to-ask (OTA) and ask-to-close (ATC) indicates that a significant positive return is observed only in the OTA period but not in the ATC period. This study also finds that the positive returns observed on the first trading day continue for up to two weeks of trading (CAR=4.43%). Findings of this study provide a better understanding of the performance of the IPO companies at two different stages, namely the initial issue stage and post-issue stage. A better understanding of the IPO performance can help investors to plan their future investment strategy by identifying the best time to purchase the IPO shares to take advantage of the significant positive initial return. The originality of this study is underscored by its meticulous methodology, tailored to the unique characteristics of the Malaysian IPO landscape, and its contribution to bridging the gap in the existing literature on short-term performance analysis in this specific context.